Analisis Hadis tentang Keadilan Orang Tua dan Implementasinya di Lingkungan 17, Kelurahan Tanjung Mulia, Kecamatan Medan Deli - Kholilah, Afni; Nasution, Muhammad Ali Azmi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
The phenomenon of parental unfair treatment of children is still found in Muslim families in Tanjung Mulia Village, Medan Deli District, particularly in the provision of affection, attention, opportunities, education, and economic support, thus revealing a gap between the principle of justice in the hadith and daily parenting practices. This study aims to analyze the concept of parental justice based on the hadith, examine the practice of justice in family life, assess its conformity with the principles of the hadith, and explain the dynamics of the interpretation of the hadith in society. A qualitative approach was used through field research with a hadith and socio-religious perspective. Data were collected through observation, interviews, and documentation, then analyzed using qualitative data analysis combined with hadith analysis of empirical findings. The results show that the principle of parental justice in the hadith includes equal treatment, balanced fulfillment of rights, objectivity, and proportional consideration of children's needs. Family practices show variations in implementation, ranging from harmonious patterns to differential treatment due to economic factors, culture, gender perceptions, birth order, child character, education level, parenting experience, and religious understanding. The interpretation of the hadith develops dynamically through family traditions, religious studies, education, and social experiences, resulting in diverse forms of implementation. This study enriches the development of family hadith studies, living hadith, Islamic family education, and strengthening parenting practices based on the principle of justice in the hadith.